2010
DOI: 10.1162/jocn.2008.21158
|View full text |Cite
|
Sign up to set email alerts
|

Attention-spreading Based on Hierarchical Spatial Representations for Connected Objects

Abstract: Abstract& Attention selects objects or groups as the most fundamental unit, and this may be achieved through a process in which attention automatically spreads throughout their entire region. Previously, we found that a lateralized potential relative to an attended hemifield at occipito-temporal electrode sites reflects attentionspreading in response to connected bilateral stimuli [Kasai, T., & Kondo, M. Electrophysiological correlates of attention-spreading in visual grouping. NeuroReport, 18, 93-98, 2007]. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
23
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 41 publications
8
23
3
1
Order By: Relevance
“…By controlling the symmetrical structure of bilateral stimuli, Kasai (2010) found that the typical P1 attention effect (150-210 ms post-stimulus onset) was obtained, regardless of the connectedness of the bilateral stimuli, but, importantly, the subsequent N1 attention effect (150-200 ms) and N2 (310/330-390 ms) showed decreases in amplitudes in the connected conditions. Note that previous studies with the bilateral-stimulus paradigm have not reported the N1 attention itself, perhaps due to a confounding of grouping factors.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…By controlling the symmetrical structure of bilateral stimuli, Kasai (2010) found that the typical P1 attention effect (150-210 ms post-stimulus onset) was obtained, regardless of the connectedness of the bilateral stimuli, but, importantly, the subsequent N1 attention effect (150-200 ms) and N2 (310/330-390 ms) showed decreases in amplitudes in the connected conditions. Note that previous studies with the bilateral-stimulus paradigm have not reported the N1 attention itself, perhaps due to a confounding of grouping factors.…”
Section: Introductionmentioning
confidence: 96%
“…Note that previous studies with the bilateral-stimulus paradigm have not reported the N1 attention itself, perhaps due to a confounding of grouping factors. The results of Kasai (2010) suggested that, since connectedness was irrelevant to the task, spatial attention was obligatorily spread or guided to the opposite side of the object region to the task-relevant side. Furthermore, the specific stimulus manipulations (unconnected, weakly-connected, and strongly-connected conditions) led to the following interpretation: N1 is associated with the extent of perceptual grouping because the attention effect diminished as connectedness increased, and N2 is associated with the unity of an object because the attention effect diminished for connected objects regardless of the degree of connectedness.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations